Innovative Governance Dalam Pengembangan Program Desa Mandiri Sebagai Upaya Pembangunan Berkelanjutan Di Desa Bongkasa Pertiwi, Kecamatan Abiansemal, Kabupaten Badung - Ni Nyoman Citra Rahayu Trisna Ari Canti; I Ketut Winaya; I Dewa Ayu Putri Wirantari (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2024)
Bongkasa Pertiwi Village is one of the villages that is developing innovation by utilizing the village's potential for community welfare. However, during the implementation of the Independent Village Program there were still problems that occurred, such as: a lack of policies governing innovation, a lack of community understanding and participation, and the existence of community groups that no longer carried out activities. This research aims to determine the Innovative Governance carried out in the development of the Independent Village Program in Bongkasa Pertiwi Village. The problem study uses indicators of Innovative Governance theory proposed by Rogers in Suwarno (2008). The research is a type of descriptive qualitative research. The author obtained data by conducting interviews, observations and documentation which were then analyzed using the Miles and Huberman analysis model. The research results show that the development of the Independent Village Program in Bongkasa Pertiwi Village can be categorized as Innovative Governance or innovative governance. However, the Bongkasa Pertiwi Village government still needs to make improvements to increase community participation and understanding. This can be achieved by improving governance through increasing collaboration and program evaluation.